Characterization of a Blood Spot Creatine Kinase Skeletal Muscle Isoform Immunoassay for High-Throughput Newborn Screening of Duchenne Muscular Dystrophy. (6th January 2020) - Moat, Stuart J; Korpimäki, Teemu; Furu, Petra; Hakala, Harri; Polari, Hanna; Meriö, Liisa; Mäkinen, Pauliina; Weeks, Ian
Abstract: BACKGROUND: Duchenne muscular dystrophy (DMD) is a progressive, lethal X-linked neuromuscular disorder with an average worldwide incidence of 1:5000. Blood spot creatine kinase (CK) enzyme assays previously used in newborn screening programs for DMD are nonspecific because measured CK enzyme activity is attributable to 3 isoenzyme forms of CK (CK-MM, CK-MB, and CK-BB) and it is the CK-MM isoform that is found predominantly in skeletal muscle. CK-MM is increased in boys with DMD owing to muscle damage. We describe a sensitive and specific automated immunoassay for CK-MM to screen for DMD in blood spots. METHODS: The prototype assay was developed on the PerkinElmer GSP ® analyzer to enable high-throughput screening. CK-MM was assayed using a solid phase, 2-site immunofluorometric system. Purified human CK-MM was used to create calibrators and controls. RESULTS: The limit of blank (LOB), detection (LOD), and quantification (LOQ) values were <1, 3, and 8 ng/mL, respectively. The analytical measurement range was 4–8840 ng/mL. Interassay (n = 40) imprecision was <7% across the analytical range. Cross-reactivity was <5% for CK-MB and 0% for CK-BB. The mean recovery of CK-MM was 101% (range 87%–111%). Blood spots from newborn infants (n = 277) had a mean CK-MM concentration of 155 ng/mL and a 99th centile of 563 ng/mL. The mean blood spot CK-MM concentration from 10 cases of DMD was 5458 ng/mL (range 1217–9917 ng/mL). CONCLUSIONS: CK-MM can be reliably quantified in blood spots. The development of this CK-MM assay on a commercial immunoassay analyzer would enable standardized and high-throughput newborn blood spot screening of DMD.